Memperdagangkan Alibi dalam Perkara Keterlibatan Korupsi Menggunakan Teori Anomie dari Emile Durkheim - Amelia Indahni; Ramadhani Cassanti; Ranti Miranda uliarta Manalu (LPPM Universitas Terbuka, 2022)
The previous research has emphasized that belief systems justification can weaken perceptions of corruption, thereby possibly encouraging unfair behavior. The results of previous replicated studies show that system justification is generally negatively related to perceptions of corruption. However, they also show a negative correlation with corrupt intentions. This journal discusses the relationship between corruption and the Anomie theory which was initiated by Emile Durkheim. The results of the study prove that there are still many people who justify any means to get what they want. Many power holders commit criminal acts of corruption to enrich themselves. In fact, according to the Anomie theory, which was coined by Emile Durkheim, all these methods must be done in the right way and do not harm others, such as saving from monthly wages every month. But in fact, many people take shortcuts to achieve their goals which will certainly harm them in the future. The same thing was done by one of the employees of the Directorate General of Taxes at the Ministry of Finance, Gayus Tambunan. He was in the spotlight of the Indonesian state because the amount of balance in his account was fantastic and hard to believe. It turned out that the money he earned was not from honest results. Instead, it comes from corruption which is an illegal act or is not justified by the state. What the state can do is to take precautions. Prevention can be done by the state by communicating values ​​and moral concepts that apply equally to all members of society. If society or the state establishes clear and unequivocal standards, individuals recognize them and abandon certain desires that they had previously planned. It can be said that, according to Durkheim, it is the communication of clear and firm social norms on the one hand and the stability of economic and social factors in society on the other that can prevent the spread of crime, especially corruption. Penelitian sebelumnya telah menekankan bahwa pembenaran sistem kepercayaan dapat melemahkan persepsi korupsi sehingga mungkin mendorong perilaku yang tidak adil. Hasil studi replika sebelumnya menunjukkan sistem justifikasi umumnya berhubungan negatif dengan persepsi korupsi. Namun, mereka juga menunjukkan korelasi negatif dengan niat korupsi. Jurnal ini membahas hubungan antara korupsi dengan teori Anomie yang digagas oleh Emile Durkheim. Hasil penelitian membuktikan banyak pemegang kekuasaan melakukan tindak pidana korupsi untuk memperkaya diri. Padahal, menurut teori Anomie yang dicetuskan oleh Emile Durkheim, semua cara tersebut harus dilakukan dengan cara yang benar dan tidak merugikan orang lain. Kenyataannya, banyak orang yang mengambil jalan pintas untuk mencapai tujuannya yang tentunya merugikan mereka di kemudian hari. Hal senada juga dilakukan salah satu pegawai Direktorat Jenderal Pajak Kementerian Keuangan, Gayus Tambunan. Ia menjadi sorotan negara Indonesia karena jumlah saldo di rekeningnya yang fantastis dan sulit dipercaya yang ternyata merupakan hasil korupsi. Yang bisa dilakukan negara adalah melakukan tindakan pencegahan. Pencegahan dapat dilakukan oleh negara dengan mengkomunikasikan nilai dan konsep moral yang berlaku sama kepada seluruh anggota masyarakat. Dapat dikatakan bahwa, menurut Durkheim, komunikasi norma-norma sosial yang jelas dan tegas di satu sisi dan stabilitas faktor-faktor ekonomi dan sosial dalam masyarakat di sisi lain dapat mencegah penyebaran kejahatan, khususnya korupsi.